The KONTRIBUSI KENDARAAN PRIBADI TERHADAP KEMACETAN JALAN PERKOTAAN (Studi Kasus di Kota Palembang) - Yusri Bermawi; A. Latif; Moch. Absor; Nandy Bosky; Ahmad Muji; M. Dian Wahyudi; Windy Permatalia (Politeknik Negeri Sriwijaya, 2022)
Palembang City is the capital of South Sumatra Province, which means it is the center of activity for all aspects of the Province of South Sumatra. Therefore, the city of Palembang becomes crowded and congested, especially the traffic flow in Palembang City. As a result, various lints traffic problems have emerged in Palembang City, one of the causes of traffic problems in Palembang City is due to the increasingly massive growth of private vehicles in Palembang City. This study aims to see the extent to which personal contributions to vehicles with road congestion in Palembang City, with traffic races such as volume, speed, and density as indicators to determine the extent to which private vehicles contribute to road congestion in Palembang City, and determine the volume, velocity, and density relationships using the greenshield method.The research method used by making direct observations on Jalan Kol. H. Burlian and Jalan Jendral Sudirman by manual method and the use of video cameras for accuracy of vehicle traffic data, data processing permits or to process data analysis using data obtained from direct observation. From the results of observations and analysis, it was found that the proportion of the volume of private vehicles on Jalan Kol. The total volume of all vehicles was 57.84%, while the percentage of the volume of private vehicles on Jalan Jenderal Sudirman to the total number of vehicles was 65.81%. The average speed of private vehicles on Jalan Kol. H. Burlian is 37.48 km / hour, while the average speed of private vehicles on Jalan Jenderal Sudirman is 33.31 km / hour. The average speed value of private vehicles on Jalan Kol. H. Burlian and Jalan Jenderal Sudirman are both above the average speed value of all vehicles on the two roads. Percentage of private car vehicle density, population density of vehicles on Jalan Kol. H. Burlian amounted to 60.59% of 47.89 pcu / hour, while the proportion of private vehicle density to density.Service level on Jalan Kol. H. Burlian Palembang V / C = 0.44, it includes the level of service level B, while the service level on Jalan Jenderal Soedirman V / C = 0.605, then the level of service is level C.